Association between frailty index based on laboratory tests and all‐cause mortality in critically ill patients with heart failure - Sutong Wang; Lin Wang; Yongcheng Wang; Shuli Zong; Hesong Fan; Yuehua Jiang; Xiao Li (ESC Heart Failure)
Abstract Background The frailty index based on laboratory tests (FI‐lab) can identify individuals at increased risk for adverse health outcomes. The association between the FI‐lab and all‐cause mortality in patients with heart failure (HF) in the intensive care unit (ICU) remains unknown. This study aimed to determine the correlation between FI‐lab and all‐cause mortality to evaluate the impact of FI‐lab on the prognosis of critically ill patients with HF. Methods This retrospective observational study utilized data extracted from the Medical Information Mart for Intensive Care IV database. The FI‐lab, which consists of 33 laboratory tests, was constructed. Patients were then grouped into quartiles (Q1–Q4) based on their FI‐lab scores. Kaplan–Meier analysis was used to compare all‐cause mortality among the four groups. A Cox proportional hazard analysis was conducted to examine the association between the FI‐lab score and all‐cause mortality. The incremental predictive value of adding FI‐lab to classical disease severity scores was assessed using Harrell's C statistic, integrated discrimination improvement (IDI) and net reclassification improvement (NRI). Results Among 3021 patients, 838 (27.74%) died within 28 days, and 1400 (46.34%) died within a 360 day follow‐up period. Kaplan–Meier analysis indicated that patients with higher FI‐lab scores had significantly higher risks of all‐cause mortality (log‐rank P < 0.001). Multivariable Cox regression suggested that FI‐lab, evaluated as a continuous variable (for each 0.01 increase), was associated with increased 28 day mortality [hazard ratio (HR) 1.02, 95% confidence interval (CI) (1.01–1.03), P < 0.001] and 360 day mortality [HR 1.02, 95% CI (1.01–1.02), P < 0.001]. When assessed in quartiles, the 28 day mortality risk [HR 1.66, 95% CI (1.28–2.15), P < 0.001] and 360 day mortality risk [HR 1.48, 95% CI (1.23–1.8), P < 0.001] were significantly higher for FI‐lab Q4 compared with FI‐lab Q1. FI‐lab significantly improved the predictive capability of classical disease severity scores for 28 and 360 day mortality. Conclusions In ICU patients diagnosed with HF, the FI‐lab is a potent predictor of short‐term and long‐term mortality in critically ill patients with HF. The active use of FI‐lab to identify high‐risk groups among critically ill HF patients and initiate timely interventions may have significant value in improving the prognosis of critically ill patients with HF.